Acetylation Regulating Protein Stability and DNA-Binding Ability of HilD, thus Modulating Salmonella Typhimurium Virulence. (24th February 2017) - Sang, Yu; Ren, Jie; Qin, Ran; Liu, Shuting; Cui, Zhongli; Cheng, Sen; Liu, Xiaoyun; Lu, Jie; Tao, Jing; Yao, Yu-Feng
Abstract: HilD, a dominant regulator of Salmonella pathogenicity island 1, can be acetylated by protein acetyltransferase (Pat) in Salmonella Typhimurium, and the acetylation is beneficial to its stability. However, the underlying mechanism of HilD stability regulated by acetylation is not clear. We show here that lysine 297 (K297) located in the helix-turn-helix motif, can be acetylated by Pat. Acetylation of K297 increases HilD stability, but reduces its DNA-binding affinity. In turn, the deacetylated K297 enhances the DNA-binding ability but decreases HilD stability. Under the Salmonella pathogenicity island 1–inducing condition, the acetylation level of K297 is down-regulated. The acetylated K297 (mimicked by glutamine substitution) causes attenuated invasion in HeLa cells, as well as impaired virulence in mouse model, compared with the deacetylated K297 (mimicked by arginine substitution), suggesting that deacetylation of K297 is essential for Salmonella virulence. These findings demonstrate that the acetylation of K297 can regulate both protein stability and DNA-binding ability. This regulation mediated by acetylation not only degrades redundant HilD to keep a moderate protein level to facilitate S . Typhimurium growth but also maintains an appropriate DNA-binding activity of HilD to ensure bacterial pathogenicity.